An Explorative Biomarker Study for Vaccine Responsiveness after a Primary Meningococcal Vaccination in Middle-Aged Adults - van der Heiden, Marieke; Berbers, Guy A. M.; Fuentes, Susana; van Zelm, Menno C.; Boots, Annemieke M. H.; Buisman, Anne-Marie (Frontiers in Immunology, 2018)
Introduction: Prevention of infectious diseases in the elderly is essential to establish healthy ageing. Yet, immunological ageing impairs successful vaccination of the elderly. Predictive biomarkers for vaccine responsiveness in middle-aged adults may help to identify responders and non-responders before reaching old age. Therefore, we aimed to determine biomarkers associated with low and high responsiveness towards a primary vaccination in middle-aged adults, for which a tetravalent meningococcal vaccine was used as a model. Methods: Middle-aged adults (50-65 years of age, N=100), receiving a tetravalent meningococcal vaccination, were divided into low and high responders using the functional antibody titers at 28 days post-vaccination. A total of 48 parameters, including absolute numbers of immune cells and serum levels of cytokines and biochemical markers, were determined pre-vaccination in all participants. Heat maps and multivariate redundancy analysis (RDA) were used to reveal immune phenotype characteristics and associations of the low and high responders. Results: Several significant differences in pre-vaccination immune markers were observed between the low and high vaccine responders. Moreover, RDA analysis revealed a significant association between the pre-vaccination immune phenotype and vaccine responsiveness. In particular, our analysis pointed at high numbers of CD4 T-cells, especially naïve CD4 and Treg subsets, to be associated with low vaccine responsiveness. In addition, low responders showed lower pre-vaccination IL-1Ra levels than high responders. Conclusion: This explorative biomarker study shows associations between the pre-vaccination immune phenotype and vaccine responsiveness after a primary meningococcal vaccination in middle-aged adults. Consequently, these results provide a basis for predictive biomarker discovery for vaccine responsiveness that will require validation in larger cohort studies.